Trace Metal Distribution in Surface Water, Sediment, and Tissues of Freshwater Catfish (Clarias. Gariepinus), From Oke- Afa Canal, Lagos Nigeria - O.J, Aderinola; V, Kusemiju; E. O, Clarke (International Journal of Geography and Geology, 2012)
This paper discusses concentrations of 7 essential trace metals (chromium,cadmium, copper, lead,nickel, manganese and zinc) in water, sediment and freshwater fish (Clarias. gariepinus) tissues from Oke-Afa Canal, Lagos Nigeria The sampling and analysis of the samples from Oke Afa canal were carried out between the month of June-October, 2011 and experimental procedures used followed the description of American Public Health Association (APHA) The results showed that Liver concentrated highest level of zinc, copper and lead (6.851±0.005 mg/Kg, 1.876±0.001mg/Kg and 0.143±0.001mg/Kg respectively). This was followed by sediments with mean values of (nickel = 0.400±0.001mg/Kg, chromium-=0.127±0.003mg/Kg, mn =0.092±0.001mg/Kg and cadmium= 0.076±0.003mg/Kg). Surface water equally concentrated some metals such as Manganese, cadmium and lead with mean values of 0.069±0.101Mg/L, 0.043±0.011Mg/L, 0.039±0.016Mg/L respectively. The order of bioaccumulation in sediment are Zn >Cu>Ni>Cr>Pb>Mn>Cd while the order of bioaccumulation in liver was Zn>Cu>Ni>Pb>Cd>Mn>Cr Also the order of concentration in surface water was Mn>Zn>Cd>Pb>Ni>Cu>Cr Metal concentration in the fish tissues (flesh, bones gills and guts) was low in concentration, but the values were still significant at 95 percent confidence limit (P< 0.05) with the exception of Manganese. This suggest that the water quality of Oke Afa canal system is adversely affected and impaired by the discharge of domestic, agricultural and industrial wastes. Comparison of these values with FAO/WHO limits in fish tissue showed that it is safe to consume the fish species from Oke -Afa canal for now but may be unsafe due to possible bioaccumulation of the metals in the organs of man since humans are at the top of food chain.